2020
DOI: 10.1080/20961790.2020.1717029
|View full text |Cite
|
Sign up to set email alerts
|

Can canines alone be used for age estimation in Chinese individuals when applying the Kvaal method?

Abstract: Due to the secondary dentin formation, the dental pulp undergoes changes in shape throughout life. Based on this phenomenon, the Kvaal method has been applied to various populations for age estimation, and its usefulness has been verified. When applying the Kvaal method to Chinese subjects, we observed a relatively strong correlation between mandibular canines and age. This study notes the correlation between canines and chronological age and is the first to identify which canine is most closely related to chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…This is influenced by the style of mastication. 31,32 The results of this study are in line with the results of the study by Li, Zhao et al 31 who used the Kvaal method found that the maxillary canines in the left region had a stronger correlation than the right region.…”
Section: Discussionsupporting
confidence: 90%
“…This is influenced by the style of mastication. 31,32 The results of this study are in line with the results of the study by Li, Zhao et al 31 who used the Kvaal method found that the maxillary canines in the left region had a stronger correlation than the right region.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of teeth, mandibular first premolars, level B showed the best correlation with age [ 13 ]. Similarly, some authors who have used lengths and width measurements to calculate age have proposed that the use of width parameters without the length ratios achieves higher accuracy of results [ 12 , 13 , 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies used a combination of the Kvaal recommended six teeth with three mandibular and three maxillary teeth and a sum of six teeth [9,12,14,21]. Two studies used canines [24,29].Two studies used a combination of three mandibular and three maxillary teeth and the sum of mandibular and maxillary teeth [22,32]. One study used a combination of three mandibular teeth and three maxillary teeth [10].…”
Section: Characteristics and Quality Of The Studies Includedmentioning
confidence: 99%
“…For example, Li et al . [ 27 ] found that measured data of maxillary canines were more correlated with CA compared with other teeth in the age estimation of northern Chinese population. This study was inspired by their previous research, which found that the mandibular canines had a relatively high correlation with CA [ 18 ].…”
Section: Discussionmentioning
confidence: 99%